Workload Thresholds for Human Performance Models. (September 2017) - Steinberg, Dick; Donohoo, Dan; Strater, Laura; Diggs, Alice
Human performance modeling (HPM) can be an effective tool to use for determining crew designs. Crew design includes determining the number of operators needed, the role of automation, and member task responsibilities required to operate a system. Without effective measures of performance and thresholds for assessing success, design decisions from HPM will be erroneous. Operator tasks can be assigned and allocated to crew members in a simulation to estimate the workload for each operator during a period of performance. The methods for determining when an operator exceeds workload thresholds create challenges for those using HPM for crew design. Some types of analysis have more clearly defined thresholds. For example, if a military operator has too many tasks to complete to effectively initiate countermeasures between the times they receive a warning until the time the threat arrives, they are overloaded and cannot complete their mission. However, many missions do not have such a severe penalty for not completing the tasks within a given time. For example, pharmacists, satellite managers, traffic managers, food service workers do not have such stringent task timing completion thresholds. For example, the penalty for a food service provider to be overloaded is typically extended wait times rather than risk of a loss of life. For these types of operational situations, determining overload is much more challenging. This paper describes a new workload thresholds for operator workflow models. It incorporates the vigilance effort, the maximum time a crew member will be fully loaded, and determining the maximum time worked without a break.